Formation factors of the demographic state of the population in the Lviv city - Petrovska, M. A.; Petrovskyi, S. V. (Man and Environment. Issues of Neoecology, 2022)
Purpose. To evaluate the demographic state of the population, as well as the socio-economic and ecological factors of its formation in the city of Lviv in the light of statistical indicators and own sociological research. Methods. Statistical, comparative, questionnaire method. The processing of questionnaires was carried out with the help of the "OSA" software complex. Results. As of January 1, 2020, the permanent population of Lviv was 717,700. The average age of the population tends to increase. Due to the aging of the population, there are structural changes in the demographic load. The birth rate is "low" according to the evaluation criteria of the main demographic indicators. In Lviv, a trend towards a decrease in the mortality rate of children under 1 year was observed. Lviv is also distinguished by the number of registered marriages per 1,000 of the existing population, where this indicator is almost 3 times higher than in Ukraine. The consumer behavior of households depends on gender and age characteristics, the presence of children in the family, the level of education and characteristics of household behavior. Buying expensive goods and saving for the purpose of making a profit is not typical for families with 4 or more children. For households without children, they can afford to buy expensive goods. The total indicator of the standard of living of the population in Lviv is significantly higher, compared to the Ukrainian average and the regional average. Conclusions. The demographic state of Lviv is determined by the demogeographic position and various economic, social, cultural, religious and behavioral factors. Negative changes in certain factors increase the threat of depopulation, a decrease in the birth rate, an increase in mortality, an aging population, the burden of the elderly, and the loss of people of reproductive age.